Simultaneous chemical reactions effect on dispersion of a solute in peristaltic propulsion of a newtonian fluid in an inclined channel with wall properties - Dhange, Mallinath; Sankad, G.C. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the dispersion of a solute in the peristaltic propulsion of an incompressible and viscous fluid through a permeable medium under the influence of wall properties with simultaneous homogeneous, heterogeneous chemical reactions in an inclined uniform channel has been studied. The issue is studied through conditions of Taylor?s limit and long wavelength hypothesis. The mean effective coefficient of scattering expression is computed and outcomes are interpreted physically through graphs.
Keywords: dispersion; inclined channel; viscous fluid; peristaltic propulsion; wall properties